Les jeux de la spectature : paratextes cinématographiques des années vingt et archéologie du virtuel - Fabrice Lyczba (Transatlantica)
As early as the 1920s, the Classical Hollywood fiction film was described through two discursive formations: the discourse of entertainment and dreams on the one hand, the discourse of realism on the other hand. What are we to make of this dual critical regime, and notably of the injunction to look for realism in Hollywood fictions? Through the analysis of examples of 1920s American film paratexts that play with the question of the reality of film fictions, this article describes how this discursive formation of realism signals the emergence of a modern and playful media spectatorship. This spectatorship, revealed through publicity discourses, newspaper reports or promotional practices of 1920s cinema, is analyzed as a game, with potential hallucinatory effects, organized around the encounter of virtual worlds, worlds that are impossible yet present, unreal yet shot on real locations, ephemeral and concrete apparitions of fictional Hollywood universes that seem, however, persistent—the archeological trace of contemporary modes of virtual tele-presence. Drawing both from a semio-pragmatic analysis of modes of film reception and a narratological approach to the transactional value of paratexts, this article aims at describing the offscreen expansion of Hollywood fiction through this paratextual discursive formation of realism and to analyze it as an effort to virtualize reality and transform the space of film reception into a game interface.